Development of Earth and Space Knowledge Competencies for Science Teacher Candidates: Field-Project Based Learning Perspectives - An Nuril Maulida Fauziah; Tutut Nurita; M. Arif Mahdiannur; Putri Wahyu Ramadhani (Postgraduate, University of Mataram, 2021)
This study aims to describe the competence of Earth and space knowledge of prospective science teacher students. Learning is carried out with the perspective of Field-Project Based Learning, students are asked to make direct observations of the components of the lithosphere, hydrosphere, and atmosphere in their living environment. Competencies from observations made by students include the ability to determine objects, knowledge of objects, and understanding of objects in their environment. The results of observations carried out are reported in the form of a written report supported by personal documentation in the form of photos of objects (lithosphere, hydrosphere, atmosphere), explanations of the selected objects based on reality connected with references that have been obtained. The results of the study indicate that the ability to determine objects, understanding and knowledge of students is excellent so that learning Earth and Space Sciences is in accordance with Field-Project Based Learning